Liability for defective products in autonomous ships: implications of Directive (EU) 2024/2853 - Cabañas Area, Sara (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
The introduction of autonomous ships in the maritime sector marks a shift from traditio-nal liability frameworks, historically centred on human error. As control increasingly shifts to automated systems, technical faults—particularly in software—gain legal significance. This paper analyses the impact of Directive 2024/2853 on defective products within maritime law, assessing its applicability to unmanned vessels and its potential to address a liability gap. It considers whether injured parties could bring claims against software developers and shipbuilders, as well as the limits and exemptions of liabi-lity. Finally, the paper explores whether autonomous navigation may lead to increased litigation under product liability regimes, given the dependency of these vessels on complex automated systems.
Keywords: autonomous ships; product liability; Directive 2024/2853; Maritime law; software defects